2018
DOI: 10.1590/1518-8345.2736.3087
|View full text |Cite
|
Sign up to set email alerts
|

Validation of vulnerability markers of dysfunctions in the socioemotional development of infants

Abstract: Objectives:to validate the vulnerability markers of dysfunctions in the socioemotional development of infants. Methods:study with a sequential exploratory mixed-method design. The vulnerability markers elaborated in the qualitative phase were analyzed by experts in the quantitative phase using the Delphi technique with a minimum consensus of 70%. Seventeen judges answered the questionnaire in the first round of analysis and 11 answered in the second round. Results:in the first round, two markers did not reach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Children who live in vulnerable environments are at greater risks of presenting difficulties in developing social, emotional, and self-perception competencies that aid them in the adoption of proper behaviors to the different contexts of society. (21) In this context, when the behavior problems started to get in the way of school activities, the mother was called. However, the solutions found for these problems resulted in a constant changing of schools until school dropout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children who live in vulnerable environments are at greater risks of presenting difficulties in developing social, emotional, and self-perception competencies that aid them in the adoption of proper behaviors to the different contexts of society. (21) In this context, when the behavior problems started to get in the way of school activities, the mother was called. However, the solutions found for these problems resulted in a constant changing of schools until school dropout.…”
Section: Discussionmentioning
confidence: 99%
“…A child's socioemotional development is related to their biological development and interactions with their environment since birth. Children who live in vulnerable environments are at greater risks of presenting difficulties in developing social, emotional, and self-perception competencies that aid them in the adoption of proper behaviors to the different contexts of society,( 21 )…”
Section: Discussionmentioning
confidence: 99%
“…Current studies on the development of measurement instruments demonstrate that a widely used approach to assess content and/or appearance validity is Content Validity Index (CVI) by item, by dimension or globally, adopting a value minimum to reach agreement, which can range from 0.70 to 0.80 (30)(31)(32)(33)(34)(35)(37)(38)(39)(40)(41)(42)(43)(44) .…”
Section: Analysis Of Results and Statisticsmentioning
confidence: 99%
“…A literature review showed that some authors recommend a committee composed of at least 5 and at most 10 professionals with clinical experience in the field and working at the time of the research (22) . Some studies that address content validation selected from 5 to 17 experts for the validation stage (29)(30)(31)33,(36)(37) .…”
Section: Population or Sample; Inclusion And Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation